Effect of Cinepazide Maleate on Serum Inflammatory Factors of ICU Patients with Severe Cerebral Hemorrhage after Surgery - Jing Zhang (Hindawi Limited, 2021)
Objective. To explore the effect of cinepazide maleate on serum inflammatory factors of intensive care unit (ICU) patients with severe cerebral hemorrhage after surgery. Methods. 116 ICU patients with severe cerebral hemorrhage treated in Taian Maternal and Child Health Hospital from June 2018 to June 2020 were selected as the research objects and randomly divided into the control group and experimental group, with 58 patients in each group. The control group was given routine treatment, while the experimental group was additionally given an intravenous drip of cinepazide maleate to compare the clinical efficacy and serum inflammatory factors between the two groups. Results. The total effective rate in the experimental group was higher than that in the control group (P<0.05). After treatment, the Glasgow Coma Scale (GCS), National Institutes of Health Stroke Scale (NIHSS), and Fugl-Meyer scores in both groups were better than those before treatment, and the scores in the experimental group were better than those in the control group (P<0.05). The oxidative stress indexes such as total antioxidant capacity (T-Aoc), superoxide dismutase (SOD), and glutathione peroxidase (GSH-PX) in the experimental group were higher than those in the control group, while malondialdehyde (MDA) in the experimental group was lower than that in the control group (P<0.05). The high-sensitivity C-reactive protein (hsCRP), interleukin-6 (IL-6), interleukin-8 (IL-8), and tumor necrosis factor-α (TNF-α) levels in the experimental group were lower than those in the control group (P<0.05). Compared with the control group, the cerebrovascular function in the experimental group was significantly improved (P<0.05), with statistically significant differences. Conclusion. Cinepazide maleate can effectively reduce the serum inflammatory factor levels of ICU patients with severe cerebral hemorrhage after surgery, alleviate the oxidative stress response in the body, and improve the cerebrovascular function and cerebral nerve function, which is worthy of clinical promotion.